Nekateri odgovori psihologije na izzive jutrišnjega dne v rehabilitaciji - Radonjič-Miholič, Vesna (Rehabilitacija (Ljubljana), 2009)
Throughout our lives we learn about ourselves, look for the meaning of our existence, set our goals and plan the ways to reach them. There are times when our lives follow our wishes but also times when events occur past or even against our wishes. Diseases and injuries can instantly change our lives completely, affect our self-respect and plant doubts on whether we can cope with the unpredictable situation. Many new challenges are added to our striving for better health. Patients need to fight the disease and its consequences and at the same time face their own fears and doubts as well as the distrust of their environment; many plans and goals become unachievable. However, it is in our psyche where immense strength is contained which can help us in most severe and apparently insolvable situations to find new values and goals, develop the remaining abilities and create the quality of life after or with the disease. Psychology is embedded into all programs of comprehensive rehabilitation and it contributes significantly to their effectiveness.
Keywords: rehabilitacija; vocational rehabilitation; psihologija; psychology